2008
DOI: 10.3354/meps07355
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of marine birds and pelagic fishes from Reunion Island as determined by stable isotope analysis

Abstract: Stable nitrogen and carbon isotopes were used to investigate trophic ecology in tropical marine bird and fish communities from Reunion Island, western Indian Ocean. Firstly, isotope signatures in the liver of Barau's petrels Pterodroma baraui, Audubon's shearwaters Puffinus lherminieri bailloni, and white-tailed tropicbirds Phaethon lepturus were used to compare their trophic levels and determine whether they forage in the same areas while breeding on Reunion Island. Spatial and trophic segregations were noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…None of the species we tracked with loggers migrate in large numbers to the tropics, so it is diYcult to be conclusive. However, feathers of some black-bellied storm petrels in our study had a similar level of 13 C enrichment to Barau's petrel Pterodroma baraui, Audubon's shearwater PuYnus lherminieri bailloni and white-tailed tropicbirds Phaethon lepturus in the tropical western Indian Ocean (Kojadinovic et al 2008).…”
Section: Inter-and Intra-speciwc Variation In Habitat Preferencesmentioning
confidence: 69%
See 1 more Smart Citation
“…None of the species we tracked with loggers migrate in large numbers to the tropics, so it is diYcult to be conclusive. However, feathers of some black-bellied storm petrels in our study had a similar level of 13 C enrichment to Barau's petrel Pterodroma baraui, Audubon's shearwater PuYnus lherminieri bailloni and white-tailed tropicbirds Phaethon lepturus in the tropical western Indian Ocean (Kojadinovic et al 2008).…”
Section: Inter-and Intra-speciwc Variation In Habitat Preferencesmentioning
confidence: 69%
“…The stable C ( 13 C) and stable N isotope ratios ( 15 N) in animal tissues reXect those of their prey during tissue formation, and values in feathers, which are metabolically inert, are Wxed thereafter (Bearhop et al 2002;Hobson and Clark 1992). Most Antarctic seabirds do not breed and moult at the same time (Hunter 1984;Marchant and Higgins 1990); hence, feathers provide critical information on diet and distribution during the nonbreeding period, when birds are far from colonies and otherwise inaccessible (Cherel et al 2000;Kojadinovic et al 2008;Quillfeldt et al 2005). The 15 N-14 N ratio ( 15 N) increases in a stepwise manner by »3-5‰ at each trophic level, whereas the 13 C-12 C ratio ( 13 C) increases to a lesser extent with trophic level (by »0.5-1‰), and can provide spatial information, including the relative reliance on an inshore versus oVshore, and benthic versus pelagic diet (Bearhop et al 2000;Cherel et al 2006;Michener and Schell 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This conforms with results from a recent study of a suite of non-breeding procellariids, showing no apparent trophic segregation between sexes in smaller species that exhibit limited or no sexual size dimorphism ). Furthermore, Kojadinovic et al (2008) suggested that the absence of large shifts in feeding behaviours of Barau's petrels from one season to another potentially indicated the use of the same preys during both breeding and non-breeding seasons, but further data on diet throughout the year are still needed to confirm this interpretation.…”
Section: Individual and Annual Variationmentioning
confidence: 86%
“…Following Schindler & Lubetkin (2004), the use of stable isotopes may follow the destinies of distinct energy sources and materials through the trophic webs, becoming, therefore, important complementary tools to analyses of food debris. Though more accurate in determining the preyed species, the evaluation of gastric contents may provide a more restrict sight about the feeding habits of the consumers, as such methods limit their analyses to shorter temporal scales (Estrada et al, 2005;Kojadinovic et al, 2008).…”
Section: Discussionmentioning
confidence: 99%